Indicadores de dotação em educandos diagnosticados com transtorno de déficit de atenção/hiperatividade - Massuda, Mayra Berto (2016)
The identification of gifted and talented students is granted by Special Education public policies. However, the identification of gifted and talented students with Attention Deficit Hyperactivity Disorder (ADHD) is a topic still little discussed nowadays. As many students with suspected TDA/H have behavioral problems and are underachievers, they may be referred by the schools to psychosocial services and, if diagnosed, they may adhere psychotherapeutic and pharmacological treatments. The similarity between characteristics of gifted and talent students and twice exceptional students (gifted or talented with ADHD), besides the lack of information on that topic, can cause erroneous or incomplete referrals and diagnosis, so that those students may not receive attendance by Special Education public policies. In this context, the teacher is shown as a major articulator to the identification of gifted and talented students, considering the coexistence of ADHD. Thus, this study aimed to: (1) verify if there could be giftedness indicators in students diagnosed with ADHD. On the second level, the study also aimed to: (1.1) collect and analyze the attitudes of teachers about giftedness; and (1.2) enable them to use the instrument in order to identify gifted students. The study was conducted in a city of São Paulo State (with approximately 70.000 inhabitants), and counted with the participation of 5 professionals from the Psychosocial Child Care Center; 3 teachers from the elementary school with at least one student diagnosed with ADHD and appointed by the center; 3 students diagnosed with ADHD; and 63 students without ADHD diagnosis from the same class of the nominated students. The method was qualitative, exploratory-descriptive, with multiple case study design. We used as research instruments: a) 2 professional characterization forms, applied to the psychosocial professionals and the teachers; b) the Likert Scale of Attitudes Toward the Identification and Development of Talent; and c) the Direct Observation in Classroom Guide. We carried out a pilot procedure with a classroom teacher and her class in order to adequate the instruments. The data analysis was descriptive with qualitative approach. Concerning the attitudes of the teachers towards the identification and the development of giftedness and talent, we noticed the permanence of myths in their speech and their need for training on that topic, mainly about the formation of giftedness and talent, the characteristics of those students, their distribution in the population, the identification instruments and appropriate attendance services. The study pointed giftedness indicators in 2 ADHD students: André, with 4 indicators on creativity and creative potential domain; and Bernardo, with 2 indicators on socioaffective domain and 1 indicator on intelligence with verbal ability domain. The third student, Carlos, hasn’t been indicated by the instrument, but he was mentioned due to his prominence in Physical Education, loosely attributed to the ADHD. Although that signalizing doesn’t guarantee the identification of those students as gifted, it is an indication of potentials that deserve attention in future evaluations and contributes to the development of methods and instruments to identify twice exceptional students.